The Eneolithic Ritual Barrow Complex in Prydnistrianske, Vinnystia Oblast: Magnetometric Surveys - Przybyła, Marcin M.; Podsiadło, Michał; Potupchyk, Mykhailo V.; Włodarczak, Piotr; Żurkiewicz, Danuta (Baltic-Pontic Studies, 2017)
The article presents the results of magnetometric surveys carried out in the village of Pridnistryanske on two barrow sites. In the site 1, the principal objectives were to capture the course of barrow ditches – not covered by the excavations – and investigate the space between the mounds. On site 2 relying on photographs was a group of nearby barrows selected for geophysical investigations.